Evaluation of the effect of a developed information tool on the knowledge of hospital outpatients on pharmacy-related laws - de Guzman, Harold Joshua D.​; Maliwat, Karl Ian H.​; Trumata, Jyna Giselle Y.​; Nacabu-an, Shiela May J.​ (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2018.)
The principal goal of pharmaceutical care is to improve the patient?s quality of life. In order to promote the welfare of patients, certain rules are in place such as Republic Act 10918: Philippine Pharmacy Act, RA 6675: Generics Act of 1988, and RA 9994: Expanded Senior Citizens Act of 2010 among others. Non-compliance to the laws governing the practice can lead to medication errors. Therefore, compliance among pharmacists to these set of rules is vital. Consequently, patients must know the rules in pharmacy practice that are relevant to them and their rationale in order for these patients follow them. The study aims to develop and evaluate the effect of pamphlets as information dissemination tools on the knowledge of PGH outpatients on select provisions of pharmacy laws. It has a quasi-experimental design involving a one-group pretest and posttest of the samples without a control group. The respondents were asked to answer a pretest prior to reading the pamphlet and a posttest was given after being given ample time to read the pamphlet. A paired t-test for the pretest and posttest mean scores was done to evaluate if the pamphlet intervention improves the knowledge of the respondents. Results show that there was an increase in mean scores from pretest to posttest. 64.77% of the respondents garnered a net gain in scores. Sex and income were found to have a statistically significant relationship with knowledge gain. Questions about RA 9994 had the highest increase in mean score while questions about RA 6675 had the lowest. The pamphlet therefore provided a statistically significant effect by increasing the knowledge scores of the tertiary level hospital outpatients on select provisions of pharmacy-related laws. It is recommended that the actual practices of these respondents be also assessed if increase in knowledge is equivalent to respondents? actions.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, May 2018.
Keywords: Pharmacy--Law and legislation